2021
DOI: 10.1519/jsc.0000000000003968
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Impact of a Single Serving Slow Absorption Carbohydrate on Metabolic, Hemodynamic, and Performance Markers in Endurance Athletes During a Bout of Exercise

Abstract: Davitt, PM, Saenz, C, Hartman, T, Barone, P, and Estremera, S. Physiological impact of a single serving slow absorption carbohydrate on metabolic, hemodynamic, and performance markers in endurance athletes during a bout of exercise. J Strength Cond Res 35(5): 1262–1272, 2021—The purpose of this study was to determine how a slow-absorbing carbohydrate affected markers of metabolism, hemodynamics, and performance in well-trained endurance athletes. We examined total and exogenous carbohydrate oxidation (CHO ox),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Therefore, subjects recognized the mixed and pre-exercise test as having a relatively low exercise intensity compared to the placebo or half-time test in the first half of the exercise protocol. It is commonly believed that increasing fat utilization and sparing CHO are associated with increased endurance [ 27 , 28 , 29 ]. Previous studies of long-distance athletes have shown that carbohydrates consumed during exercise increase fat oxidation rates during exercise [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, subjects recognized the mixed and pre-exercise test as having a relatively low exercise intensity compared to the placebo or half-time test in the first half of the exercise protocol. It is commonly believed that increasing fat utilization and sparing CHO are associated with increased endurance [ 27 , 28 , 29 ]. Previous studies of long-distance athletes have shown that carbohydrates consumed during exercise increase fat oxidation rates during exercise [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…2014). According to Davitt et al(11), a slow-digesting modi ed starch maintains a stable blood glucose level and an external energy supply during a 3-hour endurance run. The researchers used cornderived carbohydrate drinks with 13C-isotopic enrichment of the glucose molecules in their investigation.…”
mentioning
confidence: 99%